2006
DOI: 10.2202/1542-0485.1093
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Labeling and Trade of GMOs

Abstract: The emergence of agricultural biotechnology and the subsequent introduction of genetically modified organisms (GMOs) into the food system have been among the most controversial issues surrounding the increasingly scrutinized agri-food system. They have received considerable attention in the economics literature with the main focus being on the optimal regulatory response to products of biotechnology. This paper builds on the literature on the regulation of products of biotechnology by placing the analysis of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
(21 reference statements)
0
15
0
1
Order By: Relevance
“…One reason behind this process is related to the different welfare effects induced by GMOs on different groups of the society (see Lapan and Moschini, 2004;Veyssiere and Giannakas, 2006;Moschini, 2008). Indeed, different GMO regulations may reflect the preferences of the various groups involved in the government decisionmaking process, like consumers, farmers, and agrochemical and seed companies.…”
Section: Introductionmentioning
confidence: 99%
“…One reason behind this process is related to the different welfare effects induced by GMOs on different groups of the society (see Lapan and Moschini, 2004;Veyssiere and Giannakas, 2006;Moschini, 2008). Indeed, different GMO regulations may reflect the preferences of the various groups involved in the government decisionmaking process, like consumers, farmers, and agrochemical and seed companies.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies also show that the welfare effects of biotechnology regulation are complex. Lapan and Moschini (2004) and Veyssiere and Giannakas (2006) show that the welfare effects of GM regulation depend on consumer preferences, segregation 1 The early literature ignored this potential consumer aversion and estimated the welfare impact of biotechnology innovations measuring traditional consumer and producer surpluses (Alston et al 1995). Even when accounting for market power of innovating biotechnology companies (Moschini and Lapan 1997), studies found considerable welfare gains from the introduction of new GM products (FalckZepeda et al 2000) that were shared among consumers, farmers, and agro-chemical innovators (Moschini et al 2000).…”
Section: : "[F]rom the 1960s Through The Mid 1980s American Regulatormentioning
confidence: 99%
“…Additionally, GM regulation may entail further costs on seed companies such as segregation costs (Kalaitzandonakes et al 2007). Similarly, farmers may oppose or favor GM regulation, depending on the impact on input and output prices and whether they incur extra costs (Veyssiere and Giannakas 2006). Depending on how these different agents in the supply chain interact, the distribution of market power in the supply chain, and the political power of the different agents, different outcomes may result.…”
Section: Extensions Of the Modelmentioning
confidence: 99%
“…In 1997, the EU introduced GMO labeling policies with the purpose of guaranteeing 'the consumer's right to know', but labels carry indications other than just the presence of GM ingredients, they also give information on health factors and product diversification (Veyssiere and Giannakas, 2004). Labeling has also met environmental issues, playing a role in consumption decisions of consumers concerned by environmental factors associated with GM products (Appleton, 2000).…”
Section: Labeling Policiesmentioning
confidence: 99%